Reflections of a feminist organizational ethnographer: considering the subject matter and the research setting. Issue 3 (22nd September 2021) - Ryan, Irene
Abstract : Purpose: The purpose of this paper is to reflexively reconsider the effects of the author's pre-understandings, both academic and non-academic, on the subject matter and the research setting. The unforeseen implications of this disjuncture on our research practice and the expected deliverables are discussed. Design/methodology/approach: The paper engages in a critical, self-reflexive dialogue of a journey through a stimulating yet, uncomfortable piece of feminist, organizational ethnographic research drawing on the insights from the author's research diary. Findings: The account presented in this paper describes the problematic nature of undertaking a collaborative, reciprocal research project in the distinctive and foreign cultural landscape of the military. The author shows the importance of delving into matters of positionality and preparedness for what might emerge, as a form of closure. Practical implications: The paper provides insights into the importance of sponsors to access "the field" and our obligation as researchers to produce written deliverables. Originality/value: This paper contributes to the emerging literature on the significance of reflexivity in feminist inspired organizational ethnographies in highly gendered settings such as the military.